Implementasi Program Business Challenge dalam Meningkatkan Kreativitas dan Kemandirian Remaja Masjid Lingkungan 06 Tanah Enam Ratus - Rahma Fadillah; Azra Zafira Fahrizal; Alyanda Firzanni; Ardilla Oktaviani Br Ginting; Diva Sekawan Lia Putri (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to enhance the creativity and economic independence of mosque youth through the implementation of the Business Challenge Program in Lingkungan VI, Tanah Enam Ratus Village, Medan Marelan District. The program was initiated in response to the limited entrepreneurial knowledge and skills among mosque youth, which hindered their ability to develop productive business initiatives. The implementation involved several stages: field observation, interviews, workshops, mentoring sessions, halal product-making practices, and marketing simulations. The results indicate a significant improvement in participants’ ability to design business models using the Business Model Canvas, produce halal products (such as fried tofu “tahu walik” and “es kuwut”), and market them directly to the community. Moreover, the program instilled Islamic business values, including honesty (ṣidq), trustworthiness (amānah), and diligence (ijtihād), as the foundation for ethical entrepreneurship. Overall, the Business Challenge Program effectively fostered creativity and self-reliance among mosque youth while strengthening the role of mosques as centers for community empowerment.